Realización de un documental para la concientización de la donación de órganos en el Ecuador - Pesántez Vásquez, Michelle (2019)
Organ donation has been a taboo subject in Ecuadorian society because there are different mistaken beliefs around the subject. The lack of information has been an impediment for many people to know that through this process they can save and improve the quality of life of many people. The documentary to be made has the objective of informing people about this topic, and encouraging them to accept organ donation. In addition to having few works done in our country about this subject.